On strictly convex and strictly 2-convex 2-normed spaces II. (1992) - Lin, C.-S.
Abstract : In this paper a new duality mapping is defined, and it is our object to show that there is a similarity among these three types of characterizations of a strictly convex2 -normed space. This enables us to obtain more new results along each of two types of characterizations. We shall also investigate a strictly2 -convex2 -normed space in terms of the above two different types.